Ethnicity and Democracy: Managing Political Complexities in West Papua - Sasmita, A Sudiana (Universitas Islam Internasional Indonesia (UIII), 2023)
This paper aims to reveal the relationship between ethnicity and democracy in the regencies of South Sorong in West Papua Province and Keerom in Papua Province, both situated in Indonesia’s easternmost island of Papua. By using Madisonian practice to examine the ethnic party and separatist logics in both regencies, this study explores the presence of cooperation, representation, and accommodation between ethno-religious identities in South Sorong, as well as between Indigenous Papuans (orang asli Papua) and the majority Muslim non-Papuan migrants (pendatang) in Keerom. The findings of this qualitative study suggest that there is a relationship between ethnicity and democracy that can be used in a positive way for promoting peace and resolving conflict.